Calvin between facilis brevitas, confessio, and institutio: instruction of faith in Geneva - Kayayan, E. (Koers, 2009)
This article focuses on catechetical instruction in Geneva under Calvin, taking the 1537 “Instruction” and the 1545 “Catechism” as objects of study. The relationship among three key notions – Calvin’s own ideal of striving for brevity and simplicity on the one hand, the notions of “confessio” and “institutio” on the other hand – serves as catalyst to approach the nature of this cate-chetical instruction. After a historical overview of the circum-stances amidst which the above-mentioned writings were produced, a comparative study of their internal organisation leads to the assessment of Calvin’s method of theological exposition when dealing with the law and the Apostle’s Creed.